Electric Pendulum Sensor (Experimental Identification of Pendulum at Rest) - Crivoi, Dumitru; Olenici, Dimitrie (European Journal of Applied Sciences, 2023)
Background: Science works according to the scheme: hypothesis-prediction-deny-reject the hypothesis. The rejection of the hypothesis is based on direct observation data, respectively, experiment. In the case of experiments with the pendulum, an association is made between different astronomical events that take place during (around) the experiment (conjunction, eclipse, opposition, etc.) and the unexpected results, namely: the eclipse effect, the moon-solar effect, the Syzygy effect, etc. We built experiments in the period around (duration) of some astronomical events and following the analysis of the collected data, unexpected results (anomalies) were highlighted. The systemic analysis of the results of the experiments highlighted three interacting subsystems as parts of a complex system that will facilitate the experimental identification of the pendulum. Objectives: Identifying the structure, organization and non-gravitational functions of the pendulum in rest Method(s): Experimental identification. c) Results: Structure, organization and non-gravitational functions of the pendulum in rest. Conclusion: The pendulum in rest fulfills the conditions of a non-gravitational sensor (electric, magnetic, electromagnetic, etc.).